2012
DOI: 10.1172/jci62676
|View full text |Cite
|
Sign up to set email alerts
|

PES1 promotes breast cancer by differentially regulating ERα and ERβ

Abstract: The initiation of breast cancer is associated with increased expression of tumor-promoting estrogen receptor α (ERα) protein and decreased expression of tumor-suppressive ERβ protein. However, the mechanism underlying this process is unknown. Here we show that PES1 (also known as Pescadillo), an estrogen-inducible protein that is overexpressed in breast cancer, can regulate the balance between ERα and ERβ. We found that PES1 modulated many estrogen-responsive genes by enhancing the transcriptional activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 61 publications
4
103
0
Order By: Relevance
“…Our previous results and other investigators' results showed that PES1 as a transcriptional factor could be recruited to the promotors of Cyclin D1 and heme oxygenase-1 genes and directly regulated the expressions of these genes [16,31]. Here we showed that PES1 changed the expression of genes related to cell cycle and angiogenesis such as Cyclin D1, p21WAF1, HIF1a and VEGF.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our previous results and other investigators' results showed that PES1 as a transcriptional factor could be recruited to the promotors of Cyclin D1 and heme oxygenase-1 genes and directly regulated the expressions of these genes [16,31]. Here we showed that PES1 changed the expression of genes related to cell cycle and angiogenesis such as Cyclin D1, p21WAF1, HIF1a and VEGF.…”
Section: Discussionsupporting
confidence: 71%
“…Previous researches showed that pescadillo was necessary in biogenesis of ribosome and played an essential role in cell proliferation and cell cycle [7][8][9][10][11][12][13][14]. It has been shown that pescadillo could immortalize or transform some kinds of mammalian cells [15,16]. Our previous researches and other investigators' researches showed that PES1 was overexpressed in many kinds of human cancer such as malignant astrocytomas and glioblastomas [6], breast cancer [16][17][18], prostatic cancer [19,20], head and neck squamous cell cancer [21], colon cancer [22], ovarian cancer [23], neuroblastoma [24] and gastric cancer [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anchorage-dependent cell proliferation was analyzed by crystal violet assay as described previously (14). For the anchorage-independent growth assay, cells (1x10 3 ) were seeded in a 12-well plate, with a bottom layer of 0.7% low-melting temperature agar in DMEM and a top layer of 0.35% agar in DMEM.…”
Section: Plasmids and Small-interfering Rnas (Sirnas)mentioning
confidence: 99%
“…Overexpression of CUEDC2 could contribute to this discordance. PES1 (also known as Pescadillo), an estrogen-inducible protein [166] …”
Section: Ubiquitination Of Estrogen Receptormentioning
confidence: 99%